Bilingual Advertising in Melbourne Chinatown - Chen, Sherry Yong (Journal of International Students, 2014)
This paper explores the function of bilingual advertising by analyzing a case study of bilingual advertising in the Chinatown of Melbourne, Australia. The use of bilingual advertising in an immigrant setting differentiates itself from those in Asian settings where English is not used by dominant proportion of speakers in the society, and this phenomenon has its significance from a sociolinguistic perspective. In this paper, I will adopt the concept of “linguistic landscape” to discuss in detail the general functions of bilingual advertising. By integrating the theories into my case study, I aim to demonstrate how the Chinese and English versions of bilingual advertisements in Melbourne’s Chinatown differ in literal meaning, and to explain why they are designed this way.